Human Resource Management Program Development Project: Strategy for Developing Vocational High School Teacher Competence through Learning Communities - Ely Jayaningrum; Ainur Rifqi; Nuphanudin; Syunu Trihantoyo (Jurnal Penelitian Pendidikan IPA, 2026)
The gap between national human resource development policies and teacher professional development practices in vocational schools is the main background of this research. This study aims to develop the "OK Bebas Shopping" (Optimization of Workshop-Based Learning Communities and Teacher Professional Collaboration) program to address the decline in teacher competency and performance at SMKN 1 Grati. The main problems identified include low Learning Community (Kombel) engagement, weak governance, teacher age, and limited access to professional development due to unstructured independent learning policies. Using Research and Development (R&D) methods, this research went through the stages of needs analysis, planning, program development, and evaluation. The research subjects included all teachers and management of SMKN 1 Grati. The developed program systematically integrated routine workshops, community discussions, lesson study, and online training (PMM). The results showed that this program was able to transform the human resource development paradigm from a top-down approach to a sustainable community-based approach. The implementation of peer teaching and mentoring strategies proved effective in increasing teacher motivation according to Herzberg's theory and strengthening the Professional Learning Community (PLC). The program's success was measured by teacher participation (>80%) and improved learning quality. It is concluded that the management of Kombel which is planned in a managerial manner and supported by a reflective monitoring system is a strategic solution in aligning national policies with field practices to improve the quality of vocational education.